Penerapan Metode Cost Significant Model pada Estimasi Biaya Pembangunan Peningkatan Jalan - Ganjar Jojon Johari; Muhammad Rifqy Almuhsy (Institut Teknologi Garut, 2024)
Indonesia is intensively developing various infrastructure such as buildings, mosques, roads, bridges, dams and much more. Detailed planning is needed so that construction runs smoothly and results are maximum, including planning the budget (RAB). One method that can help identify significant costs in construction projects is the Cost Significant Model Method. The Cost Significant Model method is a cost analysis method that can be used to identify significant costs in construction projects. This method uses multiple linear regression analysis. In Indonesia, building district roads is a priority to improve connectivity and community welfare. Applying the Cost Significant Model in the Garut district road project is very important for efficient cost management. The aim of this research is to identify significant cost factors in district road projects and analyze the effect of implementing the Cost Significant Model on project cost management in the region. The research results show that the cost significant model provides accurate cost predictions with a coefficient of determination of 0.943, indicating a significant influence of variables on project costs. The variables Asphalt pavement division (X4) and structure division (X5) have a significant influence on project costs, so they can be prioritized to manage risks and reduce the impact of unexpected costs. The conceptual cost estimation model from this research is Y = -339907740.45 + 380172.81 (X4) + 117874.24 (X5). Testing the validity of this model shows that the cost estimation using this model is more accurate than using the average price per square meter times the building area. The Cost Significant Model method is an effective tool for managing road project costs in Garut Regency. This can help project managers predict costs more accurately and identify factors causing cost increases.